Education on Nutrition, Sanitation, and IYCF to Increase Mother's Knowledge in Lokus Stunting Village - Antun Rahmadi; Bertalina Bertalina; Sudarmi Sudarmi; Aprina Aprina (Universitas Aisyah Pringsewu, 2022)
Stunting is a condition of growth failure on children under five only years caused by chronic malnutrition. Stunting is caused by multi-dimensional factors, not due to malnutrition in pregnant women and toddlers. The research aims to prove the influence of education on nutrition, sanitation, and also infant and young children feeding (IYCF) on increasing maternal knowledge. This type of research is experimental research using quasi experiment approach with non randomized control group pre-test– post test design research. The study population was mothers who had children aged 0 to 5 years. The variables studied were education on nutrition, sanitation, and IYCF. The test of differences in knowledge before and after the intervention in each group used statistical paired t-test.The results showed that there were differences in nutritional knowledge in the control group and intervention group (p-value=0,006 and 0,0001). There was no difference in sanitation knowledge in the control group (p-value=0,208) but there was difference in sanitation knowledge in the intervention group (p-value=0,669). There was no difference in IYCF knowledge in the control group (p-value=0,083) and there was a difference in IYCF knowledge in the intervention group (p-value=0,001). Height for age before and after intervention with p value 0.018 in the intervention group. There was no difference in maternal knowledge about nutrition, sanitation and IYCF before and after the intervention between the control and intervention groups, at the initial measurement with p-values 0.309, 0.991, 0.915 and the final measurements with p values of 0.289, 0.150 and 0.753 There was no difference in Z-score weight for age before and after between control and intervention groups with p value of 0.531 and there was no difference in z-score height for age between before and after intervention with p value 0.616. Based on the research results, it is hoped that local governments and related sectors will create innovative programs that can increase the scope of appropriate infant and ypung child feeding practices, including breastfeeding and complementary breastfeeding. In addition, the puskesmas is expected to increase cooperation among health workers in providing education related to IYCF and maximizing coaching activities for posyandu cadres in the context of increasing family assistance as an effort to prevent the incidence of stunting in toddlers from pregnancy.